2013
DOI: 10.1080/14790718.2012.708037
|View full text |Cite
|
Sign up to set email alerts
|

Multilingual Stroop performance: Effects of trilingualism and proficiency on inhibitory control

Abstract: Previous research suggests that multilinguals’ languages are constantly co-activated and that experience managing this co-activation changes inhibitory control function. The present study examined language interaction and inhibitory control using a colour-word Stroop task. Multilingual participants were tested in their three most proficient languages. The classic Stroop effect was detected in all three languages, with participants performing more accurately on congruent than on incongruent trials. Multilingual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 59 publications
4
34
0
Order By: Relevance
“…It has been shown that, with better language skills, it is in fact more difficult to inhibit irrelevant material. Automatic activation of the word meaning is stronger in L1 than in L2, for example, and suppressing this activation requires cognitive resources (Marian et al, 2013;see also Gernsbacher, 1993). Favreau and Segalowitz (1983) showed that less-skilled L2 users benefited from a priming effect (e.g., were quicker to recognise the word "apple" when preceded by "fruit" rather than by "furniture") only when there was enough time to consciously process the material (1150ms).…”
Section: Attentional Processesmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that, with better language skills, it is in fact more difficult to inhibit irrelevant material. Automatic activation of the word meaning is stronger in L1 than in L2, for example, and suppressing this activation requires cognitive resources (Marian et al, 2013;see also Gernsbacher, 1993). Favreau and Segalowitz (1983) showed that less-skilled L2 users benefited from a priming effect (e.g., were quicker to recognise the word "apple" when preceded by "fruit" rather than by "furniture") only when there was enough time to consciously process the material (1150ms).…”
Section: Attentional Processesmentioning
confidence: 99%
“…Repetition (REP) repeating items, subject to individual differences and strategic use (e.g., Kahng, 2014;Peltonen & Lintunen, 2016) 7. Inhibition difficulties (INH) difficulty with suppressing irrelevant information are proposed to be connected with more advanced skills as the automatic activation is stronger (Marian et al, 2013;Jones et al, 2008) 8. Set-shifting (SHIF) * only in RAS task set-shifting is more difficult with stronger activation and may be easier with less proficiency; e.g., switching from activated letters to numbers (Segalowitz & FrenkielFishman, 2005) …”
Section: Pronunciation Problems (Pron)mentioning
confidence: 99%
See 3 more Smart Citations